Suzuki-Miyaura cross-coupling of 3, 4-disubstituted 5-bromoisoxazoles: An efficient access to trisubstituted isoxazoles. (6th July 2021) - Tsuda, Masato; Morita, Taiki; Nakamura, Hiroyuki
Graphical abstract: Highlights: Suzuki-Miyaura cross-coupling of 3, 4-substituted 5-bromoisoxazoles at C5 position. Use of bulky phosphine ligands increase the yields of trisubstituted isoxazoles. Formation of ketone 4 is suppressed under the optimized conditions. Abstract: The Suzuki-Miyaura cross-coupling of 3, 4-disubstituted 5-bromoisoxazoles 1 at the C5 position has successfully proceeded in the presence of Pd2 (dba)3 and P( t- Bu)3 ·HBF4 catalysts to give the corresponding trisubstituted isoxazoles 3 in good to high yields while suppressing the formation of ketone 4 as a byproduct. The use of bulky phosphine ligand P( t -Bu)3 ·HBF4 is essential for the current transformation, and the formation of ketone 4, which was a major product in the previous report, was able to be suppressed under the current conditions.